The effects of acute tryptophan depletion and serotonin transporter polymorphism on emotional processing in memory and attention - Roiser, Jonathan P. (2006)
Polymorphism at the serotonin transporter linked polymorphic region (5-HTTLPR) has been associated with neuroticism, increased risk for affective disorders and greater vulnerability to mood change following serotonin (5-HT) depletion. The aim of the present study was to investigate whether the cognitive effects of 5-HT depletion were differentially affected by genotype at the 5-HTTLPR polymorphism, using neuropsychological measures of memory and attention. We utilised the acute tryptophan depletion (ATD) technique to temporarily reduce 5-HT synthesis in two groups of healthy volunteers pre-selected on the basis of 5-HTTLPR genotype, 15 of the ll genotype and 15 of the ss genotype, in a double-blind, placebo-controlled crossover design. As expected, ATD resulted in a robust reduction in plasma tryptophan concentration in both genotype groups. However, the genotype groups differed in terms of the effect of ATD on cognitive performance. The ss genotype group showed impaired verbal recall following depletion, while episodic memory was unimpaired by ATD in the ll genotype group. Averaging across depletion condition, the ss genotype group outperformed the ll genotype group on tests of episodic memory and attention. Neither group was significantly affected by ATD on measures of emotional state. These data confirm previous reports that ss individuals are particularly vulnerable to 5-HT depletion, but extend these findings to the cognitive domain. The unexpected finding that ss volunteers showed improved memory and attention relative to ll volunteers suggests a possible evolutionary advantage to possession of the s allele, which may offset the disadvantage of vulnerability to depression following stressful life events.